Analisis Respon Aktivitas Belajar Siswa Dalam Pembelajaran Geografi Berbasis Artificial Intelligence Di SMA Negeri 2 Gorontalo - Wirtawati Isima; Fitryane Lihawa; Masruroh Masruroh (Universitas Negeri Gorontalo, 2026)
The integration of Artificial Intelligence (AI) in education has created new opportunities to improve student engagement and learning activities. This study aims to analyze students’ learning activity responses in AI-based Geography learning at SMA Negeri 2 Gorontalo. The research employed a Classroom Action Research (CAR) approach involving students of class XI-4. Data were collected through observation sheets, documentation, questionnaires, and learning activity assessments. The results showed that in Cycle I, student learning activity reached 71.97% in the good category, although some students were still in the adaptation stage and had not yet optimally utilized AI as a learning resource. In Cycle II, student learning activity increased to 80.30% in the very good category, marked by greater student engagement in discussions, information exploration, problem-solving, and group presentation activities. The improvement of 8.33% from Cycle I to Cycle II indicates that AI-based learning integrated with Deep Learning and the Quizizz platform effectively enhanced student participation, motivation, interaction, and engagement during Geography lessons. The use of AI-assisted learning environments also facilitated personalized learning experiences and strengthened students’ understanding of disaster mitigation concepts. These findings suggest that AI can serve as an effective learning support tool in Geography education and contribute to improving student learning activities.